Eksplorasi Dunia Teknik: Menjelajahi Berbagai Cabang Teknik dan Peluang Karir di Sekolah - Prastio, Eko (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
Early understanding of the field of engineering is crucial for students in choosing an educational path and career that suits their interests and potential. The main objective of this activity is to comprehensively introduce various branches of engineering and related career opportunities to high school students. The activity is conducted through a series of interactive workshops, inspirational presentations by engineering professionals, and in-depth question-and-answer sessions. The engineering fields covered include Environmental Engineering, Chemical Engineering, Industrial Engineering, and Petroleum Engineering, providing a holistic overview of the role and contributions of engineers in society. Students gain deep insights into future prospects and the requirements needed. In conclusion, this activity significantly increased students' interest and understanding of the engineering field. The recommendation is to integrate a more extensive and structured engineering career exploration program into the school curriculum to effectively guide students toward appropriate career choices.